Wheezing and itching: The requirement for STAT proteins in allergic inflammation - Glosson, Nicole L. (Landes Bioscience, 2012)
The development of allergic inflammation requires the orchestration of gene expression from the inflamed tissue and from the infiltrating immune cells. Since many of the cytokines that promote allergic inflammation signal through hematopoietin family receptors, the Signal Transducer and Activator of Transcription (STAT) family have obligate roles in pro-allergic cytokine-induced gene regulation in multiple cell types. In this review, we summarize work defining the contribution of each of the STAT family members to the development of allergic inflammation, using data from mouse models of allergic inflammation, studies on patient samples and correlations with single nucleotide polymorphisms in STAT genes.